Discovery of Natural Product‐Based Fungicides (II): Semisynthesis and Biological Activity of Sarisan Attached 3‐Phenylisoxazolines as Antifungal Agents. Issue 12 (19th November 2020) - Liu, Zhiyan; Cao, Jiangping; Yan, Xiaoting; Cheng, Wanqing; Wang, Xiaoguang; Yang, Ruige; Guo, Yong
Abstract: Many phytopathogenic fungi cause severe damage to crop yields. In continuation of our research aimed at the discovery and development of natural products‐based fungicides, a series of thirty‐one sarisan attached 3‐phenylisoxazolines were synthesized and evaluated for their antifungal activities against five phytopathogenic fungi ( B. cinerea, C. lagenarium, A. solani, F. solani, and F. graminearum ). Among all title sarisan derivatives, compounds IV2, IV14 and IV23 showed potent antifungal activity against some phytopathogenic fungi. In particular, compound IV2 exhibited a broad‐spectrum and more potent antifungal activity against A. solani, F. solani, and F. graminearum than the commercial fungicide Hymexazol. In addition, compounds IV2, IV14 and IV23 also displayed relative low toxicity on normal NRK‐52E cells. This work will give some insights into the development of sarisan derivatives as new fungicide candidates in plant protection. Abstract :